Aplikasi Permainan Edukasi Aksara Jawa Sebagai Media Perubahan Menuju Tantangan Digitalisasi Pendidikan - Irsyaad Cahyo Wibowo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
On the island of Java, the language that is the community's communication medium is Javanese. On the island of Java itself, there is a language that is a medium of communication for the Javanese people, namely Javanese. In language there is an aspect that complements it, namely Javanese script. However, not many people on the island of Java understand Javanese script, including even students who take Javanese script subjects. Judging from the interview study I conducted with one of the teaching staff at SDN 2 Grogol Kediri, teaching Javanese script during Javanese language subjects in class was considered boring and difficult to accept and the children were less interested. The right media according to learning objectives will be able to improve the learning experience so that students can improve their learning outcomes. This learning media panel is intended to improve students' abilities in Javanese script, including research and development, this research and development is also called Research and Development or RnD. Educational game tools (APE) are games that are specifically designed for educational purposes. Educational games are all forms of games designed to provide educational or learning experiences to the players, including traditional and modern games that are given educational and teaching content.